Exercise and education improve balance and quality of life in women with stress urinary incontinence - Pérez-Cimma, Nashari; Cigarroa, Igor; Zapata-Lamana, Rafael; Sepúlveda-Martin, Sonia; Espinoza-Pulgar, Pamela; Sarqui, Carla (Universidad y Salud, 2021)
Introduction: Stress urinary incontinence (SUI) has high prevalence in adult women, affecting psychological, social and functional variables, including decreased balance capacity, due to a lack of trunk movements that contribute to postural correction. Objective: To determine how a program based on pelvic floor muscle exercises and education affects static balance and quality of life of women with SUI. Materials and methods: 18 SUI female patients participated in a 12 week/10 sessions program that included pelvic floor muscle exercises and education (hygiene habits, urination, fluid intake). Static balance and quality of life were assessed before and after the intervention using postural oscillography and the International Consultation on Incontinence Questionnaire Short Form(ICQ-SF), respectively. Data were analyzed with the non-parametric Wilcoxon test. Results: The displacement area of the center of pressure in the open (p=0.027) and closed (p=0.006) subtests showed a significant reduction. Likewise, the amount of symptoms associated with SUI decreased (p=0.0001). Conclusions: Intervention improves static balance and quality of life, confirming the positive effects of this program, which can serve as a guide for health professionals who work with women with SUI.